Enhanced Adsorption of Orange II Using Cationic Surfactant Modified Biochar Pyrolyzed from Cornstalk. (15th June 2016) - Mi, Xiao; Li, Guoting; Zhu, Weiyong; Liu, Lili
Abstract : As dissolution of raw biomass is serious when used as an adsorbent, the cheap biochar pyrolyzed from biomass might be a good matrix. Raw cornstalk biochar was intentionally modified by cetyltrimethylammonium bromide (CTAB) to prepare the composite adsorbent designed for the removal of negatively charged pollutants. After modification, the removal efficiency for anionic dye Orange II (ORII) increased from 46.9% of the virgin cornstalk biochar to 99.7% of the CTAB-modified cornstalk biochar. The uptake of ORII proved to be favorable under acidic conditions but unfavorable under alkaline conditions. By nonlinear simulation, the Elovich model was the best to describe the adsorption kinetics. For linear simulation of the kinetic data, the pseudo-second-order kinetic model fitted the experimental points better than the pseudo-first-order model. Kinetic analysis indicated that the ORII adsorption process on the CTAB-modified cornstalk biochar might be chemical adsorption accompanied by ion exchange. At 298 K, the maximal adsorption capacity of the modified biochar is 26.9 mg/g by the Langmuir model. The adsorption of ORII increased with a rise in the reaction temperature. The enthalpy and entropy of the adsorption process are calculated to be 38.45 KJ mol −1 and 185.0 J mol −1  K −1, respectively. The negative values ofΔ G 0 at 288, 298, and 308 K were −14.92, −16.50, and −18.62 KJ mol −1, respectively. The above thermodynamic analysis demonstrates that the adsorption process was endothermic and spontaneous.